(untitled) (Global Journal of Human-Social Science, 2021)
The present article shows the working methodology of the project field: "Development and validation of a clean technology for the integral treatment of neutralization of effluents and metallurgical tailings in the use of calcareous agents". 1. Geological Characterization, 2. Delimitation of the area of environmental influence for legal exploitation, 3. Mapping, 4. Sampling, 5. Calculation of the volume of tailings, 6. Study of the environmental impact of legal exploitation relationships. It should be noted each one of these activities are important as part of the methodology of work in field, which one are developed in the tailing: "Cerro El Toro" which has been divided the aforementioned relationship into 73 sampling points, grouped according to the relationships: Salinas 1, Salinas 2, Salinas 3, Montoro and Melva, whose volume has been determined through the software AutoCAD Civil which has determined that tailings have the following volume: Salinas 1: 1917.5 m3, Salinas 2 : 20331.48 m3, Salinas 3 : 18375 m3 , Montoro: 668.56 m3 y Melva: 27945,5 m3; whose volume allowed the obtention of a representative sample of the tailing for been studied of their "Environmental Quality of tailing" which gives through the geochemical characterization analysis with the purpose of determining the "Real Impact" of the pollution of tailing in the mining communities of Shiracmaca and Coigobamba.